Effects of Cu, Zn and Cu-Zn addition on the microstructure and antibacterial and photocatalytic functional properties of Cu-Zn modified TiO2 nano-heterostructures - Tobaldi, D. M. (2017)
Titanium dioxide (TiO2) is well established as one of the most common photocatalysts used for many environmental, anti-pollution and antibacterial applications. However, in this work, novel photocatalytic TiO2 nanopowders were modified with additions of 1 mol% copper, zinc or copper + zinc (with various Cu: Zn ratios). These were prepared via a green sol–gel route and thermally treated at 450 C. For the first time, a direct comparison of the effects of these two modifying agents was performed, both as single and co-substitution. The compounds were thoroughly characterised by means of advanced X-ray diffraction (Whole Powder Pattern Modelling, WPPM) and spectroscopic methods (Raman and UV–vis). For functional properties, the photocatalytic activity in the gas-solid phase (nitrous oxides (NOx) and isopropanol degradation (VOCs)) was tested under UV and visible light, and antibacterial activity against Gram positive and Gram negative bacterial strains was also investigated. Neither copper nor zinc entered into the TiO2 structure, but nucleated as oxides at the surface of titania nanoparticles, thus creating a nano-heterojunction between the semiconductor materials; this also retarded the anatase-to-rutile phase transition. When comparing and contrasting their functional properties, it was found that Zn modification gave greater photocatalytic activity than that with Cu. On the contrary, for antibacterial activity, copper was shown to be a better additive. Co-modification with both metals did not improve the antibacterial behaviour, but did lead to an increase in photocatalytic activity in some cases.